Tools such as ChatGPT threaten transparent science; here are our ground rules for their use (Nature (London), 2023)
As researchers dive into the brave new world of advanced AI chatbots, publishers need to acknowledge their legitimate uses and lay down clear guidelines to avoid abuse. As researchers dive into the brave new world of advanced AI chatbots, publishers need to acknowledge their legitimate uses and lay down clear guidelines to avoid abuse. Credit: Tada Images/Shutterstock Webpage of ChatGPT, a prototype AI chatbot, is seen on the website of OpenAI, on a smartphone